Charles Goodwin Ridgely papers - Ridgely, Charles Goodwin, 1784-1848.
Correspondence, letterbook, and journal relating chiefly to Ridgely's naval career, especially his commands of the USS Erie (Sloop of war) during the War of 1812 and of the USS Constellation (Frigate) in the U.S. Navy Pacific Squadron. Subjects include the Latin American policy of the U.S. Navy, the wars of independence in Chile and Peru, and Ridgely's attitude toward Spain and the revolutionaries.
Naval officer.
Collection material in English.
Forms part of: Naval Historical Foundation collection.
Keywords: United States. -- Navy; United States. -- Navy -- Foreign service -- Pacific Area; United States. -- Navy. -- Pacific Squadron; Constellation (Frigate); Erie (Sloop of war); Chile -- History -- War of Independence, 1810-1824.; Latin America -- Foreign relations -- United States; Peru -- History -- War of Independence, 1820-1829.; Spain -- Colonies -- America; United States -- Foreign relations -- Latin America; United States -- History -- War of 1812 -- Naval operations; Naval officers